DEVELOPMENT OF INTERACTIVE LEARNING MEDIA FOR CLASS X TKJ STUDENTS AT SMK MUHAMMADIYAH 1 SUKABUMI - Faiz Hamdi; Muhammad Thariq Aziz; Dadan Rahmat (Universitas Lampung, 2020)
The purpose of this research is to develop and know the feasibility of interactive learning media in computer subjects and basic networks in class X TKJ SMK Muhammadiyah 1 Sukabumi.. The type of research used in this research is Research and Development using Borg and Gall models until the field trial stage. Data collection method used in this study is questionnaire or questionnaire method, using data collection instrument in the form of validation sheet validation sheet of material expert, media expert, and user response questionnaire. The user is a class X student of TKJ SMK Muhammadiyah 1 Sukabumi with a total of 4 people in a small class trial and 15 people in a large class trial. The product feasibility criteria developed in this study were determined with a minimum value of 3.3 out of a scale of 5 with a decent category. Media expert validation results get a score of 4.5 (very feasible), validation of material experts with a score of 4 (feasible), a small class trial assessment by 4 learners namely 4 (feasible) and a large class trial assessment by 15 learners is 4.3 (very feasible). That way, interactive learning media on Computer and Basic Network lessons are very feasible in the learning process. Keywords: interactive learning media, basic computers and networks, RDDOI: http://dx.doi.org/10.23960/jpvti.v2.i2.202001